(untitled) (Global Journal of Science Frontier Research, 2023)
We investigate a new integral transform called Saxena and Gupta transform in this paper Some important properties of this transform are also investigated Also discussed relation between Saxena Gupta transform and other integral transform like Laplace transform Elzaki transform Sumudu transform Mahgoub transform Integral transform of some elementary functions are given in table form in different section